Perinatal Mortality in Phranungklao Hospital - Suwanthananon, Boonchai (Journal of Health Science of Thailand, 1995)
This is a retrospective study of the perinatal mortality at Phranungklao Hospital from 1st October 1991 to 30th september 1994. There were 5,829 births that included 5,771live births, 58 stillbirths and 40 neonatal deaths. The perinatal mortality rate was 16.98 per 1,000 live births. The main cause of death was due to macerated stillbirths which accounted for 29.59%, the other causes of death were prematurity (23.47%), congenital malformation (20.42%), specific conditions (14.28%) and asphyxia (12.24%)